Academic Stress in English Learning: Implications for Foreign Language Teaching Methods - Zulfa Latifah Hanum; Sulis Sawali; Selnistia Hidayani; Dika Hilaldi; Yuli Rohmiyati (PT. Riset Press International, 2026)
Academic stress has become one of the most common challenges experienced by university students. Academic demands such as assignments, examinations, presentations, and deadlines often create pressure that may affect students’ learning experiences. This study aims to investigate the influence of academic stress on students’ concentration, learning motivation, and overall learning performance in English learning contexts. The study employed a descriptive research design involving 16 university students. Data were collected through a questionnaire distributed using Google Forms consisting of Likert-scale and open-ended questions. The findings indicate that academic stress significantly affects students’ concentration, motivation, and learning performance. Assignment workload, academic expectations, and deadlines were identified as the main sources of stress. The study also revealed that students adopt various coping strategies, including time management, relaxation activities, and seeking support from family and friends. The findings suggest that educators should implement supportive teaching methods and create positive learning environments to reduce academic stress and improve learning outcomes.